Analisis Pengaruh Sosialekonomi terhadap Kesejahteraan Keluarga Pekerja Migran Indonesia (PMI) Asal Provinsi Bali - Dewi, Ni Kadek Yunita Dewi; Yasa, I Nyoman Mahaendra (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Remittances are PMI's income sent from abroad to their families in the country. The problem that often occurs is that many remittances are misused by families. This study aims to analyze the effect of education level, patriarchal culture, and family income on contraceptive use and fertility as well as to analyze the effect of work experience, work skills, marital status on remittances and family welfare of PMI from Bali Province. The sampling technique used was purposive sampling method consisting of 98 respondents. Data were analyzed using descriptive analysis techniques and path analysis. The results of the study found that work experience, work skills, and marital status had a positive and significant effect on remittances. Work experience, work skills, marital status, and remittances have a positive and significant effect on family welfare. Work experience, work skills, and marital status indirectly influence family welfare through PMI remittances from the Province of Bali. Keywords: Work experience, Work skills Marital status, Remittance, Family welfare.